2012
DOI: 10.1073/pnas.1214265109
|View full text |Cite
|
Sign up to set email alerts
|

Architectural switch in plant photosynthetic membranes induced by light stress

Abstract: Unavoidable side reactions of photosynthetic energy conversion can damage the water-splitting photosystem II (PSII) holocomplex embedded in the thylakoid membrane system inside chloroplasts. Plant survival is crucially dependent on an efficient molecular repair of damaged PSII realized by a multistep repair cycle. The PSII repair cycle requires a brisk lateral protein traffic between stacked grana thylakoids and unstacked stroma lamellae that is challenged by the tight stacking and low protein mobility in gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(126 citation statements)
references
References 54 publications
(74 reference statements)
9
115
0
2
Order By: Relevance
“…It is important to note that although 70% to 80% of the protein complexes in grana are virtually immobile, the remaining protein complexes are very mobile . It is likely that the mobile fraction increases under environmental conditions that require brisk lateral protein transport through the crowded grana (Herbstová et al, 2012). In unstacked thylakoid membranes, the need to pack protein complexes tightly is not required because of the nonmodular organization of the PSI/LHCI system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that although 70% to 80% of the protein complexes in grana are virtually immobile, the remaining protein complexes are very mobile . It is likely that the mobile fraction increases under environmental conditions that require brisk lateral protein transport through the crowded grana (Herbstová et al, 2012). In unstacked thylakoid membranes, the need to pack protein complexes tightly is not required because of the nonmodular organization of the PSI/LHCI system.…”
Section: Resultsmentioning
confidence: 99%
“…The situation in native membranes of C 3 plants is more complex than in the computer simulations. For example, phosphorylation of damaged PSII subunits causes a slight overall increase in protein mobility (Goral et al, 2010;Herbstová et al, 2012) and disassembly of the supercomplex (Pesaresi et al, 2011;Tikkanen and Aro, 2012). Both could speed up lateral diffusion of damaged PSII out of the grana.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the structural relationship of grana core, grana margins and stroma lamellae is relevant for efficient PSII repair. In recent years, it has come into focus that high light stress is accompanied by changes in macroscopic thylakoid folding [39,48,49]. From these studies, a partial destacking of grana was concluded, i.e.…”
Section: Psii Repair Cyclementioning
confidence: 99%
“…By using fluorescence recovery after photobleaching (FRAP), it was measured that high light treatment increases the rate of protein exchange between different grana discs [60] and the mobility within isolated grana membranes [49]. The significance for the PSII repair cycle is given by the fact that under non-stressed conditions, protein (PSII) mobility in stacked grana is very low [60][61][62].…”
Section: High-light-induced Changes In Supramolecular Protein Organizmentioning
confidence: 99%
“…Lateral migration of damaged PSII complexes is facilitated by thylakoid membrane unfolding and PSII supercomplex disassembly. Both processes are enhanced by the phosphorylation of the PSII core subunits D1, D2, CP43, and PsbH, which is mainly mediated by the protein kinase STATE TRANSITION8 (STN8; Tikkanen et al, 2008;Fristedt et al, 2009;Herbstová et al, 2012;Nath et al, 2013b;Wunder et al, 2013). Efficient PSII supercomplex disassembly also requires the THYLAKOID FORMATION1 (THF1)/NON-YELLOW COLORING4 (NYC4)/Psb29 protein Yamatani et al, 2013).…”
mentioning
confidence: 99%